Responding to the Climate Threat Essays on Humanity"s Greatest Challenge - Yohe jacoby (Springer International Publishing AG, 2023)
This book is a collection of essays by leading climate scientists and economists. It aims to communicate the urgency and complexity of climate change and to propose meaningful ways humanity can respond to this global crisis.